Peran Audit Internal dalam Melakukan Pencegahan Kecurangan Akuntansi (Fraud) - Sukandani, Yuni; Marta, Dessy Dwi; Anggraeni, Nofiah Dwi; Zahro, Annisa Fatimatuz; Fatimah, Mia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to understand the role of internal audit in preventing accounting fraud in companies. A literature review is the tool of choice for this qualitative approach. In order to provide light on the research problem, secondary data is analysed. Based on the findings, internal auditors can evaluate a company's internal control system by analysing and testing it. Internal auditors have the responsibility to ensure that all company plans and activities run in accordance with the stated objectives, by thoroughly understanding the scope of the company's internal control